Mild cognitive impairment: Deficits in cognitive domains other than memory - Ribeiro, Filipa (2006)
Patients with mild cognitive impairment (MCI) typically present with memory complaints, but may have mild deficits in other cognitive domains. We compared the neuropsychological profiles of a series of consecutive MCI patients (n = 116) with a control group of healthy elderly subjects (n = 63). The presence of a memory deficit on delayed recall was consistent in the MCI sample, as it was an inclusion criterion in the study. Impairment on immediate recall was present in 62.6% of the patients on paragraph recall of the logical memory test and in 63.1% of the patients on the word paired-associate learning test. Remarkably, patients with MCI frequently had deficits in cognitive domains beyond memory. As much as 68.7% of the patients had deficits in temporal orientation, 30.2% had deficits in semantic fluency, 33.7% in the Token test, 23.4% in calculation, and 23.9% in motor initiative. If detailed neuropsychological testing is performed, the majority of MCI patients will have deficits in cognitive domains other than memory.